Development and Validation of GIS-Based Multi-Vulnerability Mapping for Floods and Landslides in Parung Panjang - Novi Trisman Hadi; Kharisma Wiati Gusti; Rizky Tito Prasetyo; Adita Utami (ISB Atma Luhur, 2026)
Rapid peri-urban development in Indonesia, particularly in metropolitan buffer areas such as Bogor Regency, has intensified land use change and increased vulnerability to hydrometeorological disasters. Parung Panjang Subdistrict faces significant environmental pressure from settlement expansion, industrial activity, and mining, which contribute to increased surface runoff, reduced infiltration capacity, and land instability. This study aims to develop and validate a Geographic Information System (GIS)-based model for flood and landslide vulnerability mapping to support sustainable spatial planning at the subdistrict scale. The analysis integrates remote sensing, topographic, and climatic data, while vulnerability weights were determined using the Analytical Hierarchy Process (AHP) and combined through a weighted overlay approach to produce flood, landslide, and multi-hazard vulnerability maps. Model validation was conducted using a confusion matrix, resulting in an Overall Accuracy of 88.4% and a Kappa coefficient of 0.84, indicating strong agreement. The developed flood vulnerability map was further implemented in a web-based GIS platform and functionally tested, achieving a 95% success rate. The findings show that high flood vulnerability is concentrated in low-elevation areas with high moisture indices and dense built-up land use, while multi-hazard zones identify priority areas for mitigation. This study demonstrates the integration of validated multi-hazard spatial modeling with web-based implementation, providing a practical decision-support tool for local disaster mitigation and spatial planning.